ETHNO-CULTURAL COMPONENT IN MODERN PRIMARY EDUCATION - Romaniuk, Svìtlana (Mountain School of Ukrainian Carpaty, 2023)
The aim of the article is to reveal the role of the ethno-cultural component in forming the national consciousness of junior schoolchildren. One of the most important functions of the school at today's stage is the development of the child's personal world through mastering the spiritual and practical experience and culture of humanity, educating a cultured person capable of self-determination and productive creative activity to create a cultural environment. The implementation of the ethno-cultural component of the content of school education, which is provided by the cultural approach, opens up space for students in creative and research activities, their acquisition of key and subject competencies. It has been proven that the task of the teacher and school education is to ensure the transmission and communication of the ethno-cultural traditions of previous generations to the present, support the positive trends of cultural interaction in the conditions of cohabitation of different peoples / nationalities / ethnic groups for the enrichment and development of ethnic cultures as part of the national culture. It is emphasized that the ethnocultural component is an effective means of awakening cognitive activity, independence, bright individuality, aesthetic development of junior schoolchildren, their involvement in the rich treasures of the material and spiritual culture of Ukrainian people through the assimilation of theoretical knowledge and practical participation in multiplying its achievements. It ensures the assimilation of samples and values of national culture, cultural-historical and social experience of one's state, the formation of a sense of belonging and respect for one's native land. The implementation of this component is ensured through the content of the textbooks of the linguistic and literary field of education - "Ukrainian language" and "Reading", where samples of artistic works of ethno-cultural orientation are presented, since Ukrainian studies topics form Ukrainian studies and general cultural competence in primary school students.